Одговорност даваоца услуга у европском уговорном праву и у правним системима земаља региона: општи режим - Дабовиќ Анастасовска, Јадранка, Гавриловиќ, Ненад (Правни факултет Универзитета у Крагујевцу, 2017)
The paper conducts a comparative analysis on the issue of liability of the service provider in European contract law and in the legal systems of countries in the region. The analysis first covers the existing rules of European contract law on the liability of service providers in service contracts. The said discussion is subsequently used as introductory in relation to the solutions contained in European legal projects for regulating the so called general regime of liability of the service provider. Comparatively with such rules, the paper analyzes the general rules of countries in the region concerning the liability of the service provider in service contracts. The analysis shows that the current European legislation is incomplete and fragmentary, while legislative developments demonstrate little likelihood of building a general system of liability of service providers. On the solutions of the legal systems of countries in the region, they prove to be sufficiently flexible and suited for the needs of the practice.
Liability of the service provider in European contract law and in the legal systems of countries in the region: the general regime
Keywords: services, service contract, liability, EU law, service provider